Numerical simulation of water-quality model on flooding using revised lax-diffusive and modified siemieniuch-gladwell methods - Subklay, Kanawoot; Pochai, Nopparat (My University, 2019)
In 2011, Thailand has been confronted a largest flooding. The mass of water has been drenched from many main and branch rivers to cover wide areas. The residents who lived in the flooding area have to build a manmade sandbag dike to protect their village. The flooding has been taken for a long time meanwhile the flooding water becomes contaminated. There are some residents in their flooding area want to drain their contaminated water to a nearest area. They have been destroyed their sandbag dike. Consequently, the dispute among residents is occurred. In this research, a mathematical simulation of a water-quality on a long period flooding using a couple of two models is proposed. The first model is the one-dimensional shallow water equations that provide the water elevation and velocity. The second model is a one-dimensional advection-dispersion equation that provides the water pollutant concentrations after the sandbag dike has been destroyed. A revised Lax-diffusive is used to approximate the solution of the first model. Consequently, the numerical solutions of the second model are obtained by using the traditional and modified Siemieniuch-Gladwell schemes.
Keywords: Advection-dispersion equation; Dam-break model; Dispersion model; Finite differences; Lax-diffusive scheme; One-dimensional; Revised Lax-diffusive scheme; Shallow water equations